2018
DOI: 10.1055/a-0586-3369
|View full text |Cite
|
Sign up to set email alerts
|

Inzidenz und Behandlung des nicht stoffgebundenen Delirs in deutschen Haus- und Facharztpraxen

Abstract: Zusammenfassung Ziel Über die Häufigkeit und die medikamentöse Behandlung des nicht stoffgebundenen Delirs in deutschen Haus- (HA) und Facharzt-Praxen (FA) ist wenig bekannt. Ziel der Studie war die Bestimmung der Delir-Inzidenz und der Delir-Behandlung mit Neuroleptika und Benzodiazepinen in HA.- und FA-Praxen. Methoden In dem Zeitraum von 2012 bis 2015 wurden 2.999 Patienten > 65 Jahre in 1.262 HA- und 1.425 Patienten in 203 FA-Praxen mit erstmaliger Delir-Diagnose (ICD 10: F05) ausgew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…MALAT1 upregulated BIRC5 expression to promote cell proliferation, cell cycle progression and migration yet inhibited cell apoptosis in RCC through targeting miR‐203. Besides, MALAT1 promoted OS tumour growth in vivo . Furthermore, MALAT1 regulated ovarian cancer cell proliferation, migration and apoptosis through Wnt/β‐catenin signalling pathway…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MALAT1 upregulated BIRC5 expression to promote cell proliferation, cell cycle progression and migration yet inhibited cell apoptosis in RCC through targeting miR‐203. Besides, MALAT1 promoted OS tumour growth in vivo . Furthermore, MALAT1 regulated ovarian cancer cell proliferation, migration and apoptosis through Wnt/β‐catenin signalling pathway…”
Section: Discussionmentioning
confidence: 97%
“…Besides, MALAT1 promoted OS tumour growth in vivo. 33,34 Furthermore, MALAT1 regulated ovarian cancer cell proliferation, migration and apoptosis through Wnt/βcatenin signalling pathway. 35 Our research showed that MALAT1 promoted RCC tumorigenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%